UJI EFEKTIVITAS ANTIINFLAMASI SUSPENSI EKSTRAK DAUN BAYAM DURI (Amaranthus spinosus L.) TERHADAP TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI KARAGENAN - Fauzia, Rizki Rahmah; Zuniarto, Ahmad Azrul (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2017)
Background: Leaves of Thorn Spinach are one of the plants that have pharmacological activity which are to relieve pain and as anti-inflammatory. Inflammation is a normal protective response to tissue injury caused by physical trauma, destructive chemicals, or microbiological agents. In this study, the cause of inflammation was carrageenan injected in white rat. Objective: This study aimed to determine whether extract and suspension of thorn spinach leaf extract (Amaranthus spinosus L.) was useful to decrease volume of edema and to determine concentration of extract and suspension of thorn spinach leaf extract (Amaranthus spinosus L.) decrease volume of edema in male white rat (Rattus norvegicus). Methode: Study subjects were 24 males white rat (Rattus norvegicus) with weight ± 200 grams. White rats were divided into 2 large groups with 12 rats for preliminary and 12 rats for treatment. The study was conducted for 6 hours. From the data of edema volume, were calculated AUC (Area Under the Curve) that is the area under the curve between the mean volume of edema against time and percent of anti-inflammatory power. Data were analyzed using ANOVA statistic test, and T-test. Result: The result showed that extract and suspension of thorn spinach leaf extract (Amaranthus spinosus L.) had effectiveness in decreasing the volume of edema in leg of white rat (Rattus norvegicus) and extract concentration of 50% and suspension of thorn spinach leaf extract concentration of 50% had the most effectiveness in decreasing volume of edema in leg of white rat (Rattus norvegicus) with inhibition percentage as much as 15,63% and 28,08%. Conclusion: extract and suspension of thorn spinach spinach leaf (Amaranthus spinosus L.) had effectiveness in decreasing the volume of edema in leg of white rat (Rattus norvegicus) and extract concentration of 50% and suspension of thorn spinach leaf extract concentration of 50% had the most effectiveness in decreasing volume of edema in leg of white rat (Rattus norvegicus).